HIV cell tropism: from diagnosis to viral evolution - Arif, Muhammad Shoaib [UNIFESP] (2016)
HIV-1 tropism to co-receptors CCR5 or CXCR4 relates to disease progression and cytopathic effects of the virus. Furthermore, antagonists to co-receptors have become valuable addition to the arsenal of antiretroviral drugs. Assessing co-receptor tropism is mandatory for the prescription of these drugs. Phenotypic assays are usually recommended over genotypic assays to infer co-receptor tropism. The prediction on maintaining or switching HIV-1 co-receptor usage over time is still uncertain. Here in this thesis we have presented a new phenotypic tropism assay and evaluated evolution of co-receptor tropism in two different cohorts of individuals infected with HIV-1. First, we have successfully developed a new phenotypic assay based on 450 bp C2V3 region of HIV-1 envelope. Initially, this phenotypic assay is developed with reference HIV-1 strains with known tropism and validated with the TRT phenotypic assay that uses a slightly bigger fragment (~750 bp) compared to our assay. One of the major advantages of the tropism assay developed herein is the small fragment size and the possibility of adaption to use with proviral DNA and could be used to infer tropism for individuals with plasma viral load <1,000 copies/ml. Secondly, genotypic co-relates of tropism were evaluated in a cohort of HIV-1 infected individuals after recent infection. Tropism was assessed with the Geno2pheno web portal that offers different false positive rate (FPR) cutoffs with the probability to classify an R5 tropic virus falsely as CXCR4 using virus. Geno2pheno generate results graded as FPR and can be adapted according to patient´s needs. No significant association was observed between CXCR4 using strains and viral load, CD4 counts, timing for treatment, GBV-C co-infection and HLA or clade profile. However, we were able to identify 9 individuals with a co-receptor switch to use CXCR4. 6 of these individuals remained treatment naïve during the study period. Strains with intermediate FPR were identified during evolution towards CXCR4 usage and a consistent trend of decreasing FPR over time was observed with a mean evolution time of 27.29 (range: 8.90-64.62) months. Majority of R5 viruses were observed with a baseline FPR>50% and remained R5 during the study period whereas individuals showing viruses with a co-receptor switch to CXCR4 use had baseline FPR<50%. Logistic regression analysis was performed to determine the potential of FPR to predict co-receptor switching over time. We determined that viruses with an FPR of 40.6% presented a stable FPR over time, whereas lower FPRs tend to progressively decay leading to emergence of CXCR4 using strains. The area under the ROC curve for the predicted cutoff level was 98%. Last, we have studied the impact of thalidomide use on HIV co-receptor tropism in an open label, randomized, controlled, pilot proof of concept clinical trial carried out in 30 HIV infected ART naïve male individuals. Thalidomide use resulted in a decline of CD4/CD8 ratio (p=0.08) and CD4+ T cell counts (p=0.04) in the treatment group compared to control group, however, these changes were observed to be independent of the viral type/subtype and co-receptor tropism profiles.